Experimental Analysis of Mechanical and Thermal Characteristics of Luffa/Epoxy Polymer Composite under the Influence of Nanosilica - Rajasekaran Saminathan; Haitham Hadidi; Yahya Ali Fageehi; P. Manoj Kumar; M. Venkatasudhahar; null Ankit; S. Ram; Dawit Tafesse Gebreyohannes (Advances in Materials Science and Engineering)
In the current work, the experimentations have been accomplished to assess the impact of diffusing nanosilica particles in epoxy matrix on the mechanical and thermal performance of the luffa fibre reinforced epoxy composite material. The matrix and fibre composition are fixed as 80 : 20 throughout the study, and the nanosilica is disbanded in diversified volume fractions of 0%, 0.5%, 1.0%, 1.5%, 2.0%, and 2.5%, respectively, while preparing luffa/epoxy/nanosilica (LES) composite samples. The mechanical characteristics, such as tensile, flexural, and impact behaviour of the composite, and the thermal properties, namely, thermal stability and thermal conductivity, are examined for the LES samples. The experiments are accomplished as per the ASTM standards. The results revealed that the assimilation of nanosilica particles in epoxy has improved the mechanical and thermal characteristics of the composite significantly. The tensile, flexural, and impact strength of the composite have been amended by 157.58%, 66.9%, and 16.5% with 1.5% addition of nanosilica in epoxy. Similarly, thermal conductivity of the composite is improved by 47.53% with the dispersion of 2.5% nanosilica in epoxy matrix. In addition, the thermal stability of the LES composite samples is substantially improved while disbanding nanosilica in epoxy matrix. However, the better results are reported for the LES composites containing 1.5% nanosilica content, compared to the next higher volume fractions of nanosilica content in epoxy matrix.